Impact of waste cooking oil on the viscosity, microstructure and mechanical performance of warm-mix epoxy asphalt binder. (10th August 2020) - Li, Chenxuan; Han, Xiaocheng; Gong, Jie; Su, Wufeng; Xi, Zhonghua; Zhang, Junsheng; Wang, Qingjun; Xie, Hongfeng
Highlights: Waste cooking oil (WCO) modified epoxy asphalt binder (EAB) has been developed. WCO lowers the viscosity and thus extends the construction time of the neat EAB. Phase inversion in WEAB occurs when 6 wt% WCO is added. WCO improves the low-temperature performance of the neat EAB. WCO enhances the damping properties and thermal stability of the neat EAB. Abstract: Waste cooking oil (WCO) was used as a warm mix asphalt (WMA) additive to modify warm-mix asphalt binder (WEAB) with the expectation of lowering the viscosity and prolonging the construction time of the binder. The viscosity, phase separation, viscoelasticity, thermostability and mechanical properties of WCO modified WEABs were studied and compared with the neat WEAB. WCO significantly reduced the WEAB's viscosity and extended the construction time of the neat WEAB. Moreover, the reducing and prolonging effects increased with the WCO content. Phase-inverted microstructure and secondary phase separation formed in the modified WEAB with 6 wt% WCO. The inclusion of WCO improved the low-temperature performance of the neat WEAB. The damping behavior and thermostability of the neat WEAB were improved with the inclusion of WCO. The presence of WCO increased the elongation at break of the neat WEAB when the waste oil content was lower than 4 wt%.